The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1021/la5037844
|View full text |Cite
|
Sign up to set email alerts
|

Radiolytic Method as a Novel Approach for the Synthesis of Nanostructured Conducting Polypyrrole

Abstract: In this study, a novel and extremely facile method for the synthesis of conducting polypyrrole (PPy) was achieved in aqueous solution. This radiolytic method is totally free of template and environmentally friendly compared with traditional chemical methods. According to ultraviolet-visible (UV-vis) spectroscopy and Fourier transform infrared (FTIR) spectroscopy analysis, pyrrole (Py) monomers were polymerized into PPy thanks to their oxidation by HO(•) radicals produced by the radiolysis of water when exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 52 publications
(111 reference statements)
6
53
0
Order By: Relevance
“…14 Apart from the traditional methods of polymers synthesis, ionizing radiation induced polymerization by g-rays or accelerated electrons is not commonly used in the field of CP synthesis. 15 In previous studies, our group has developed a new methodology based on radiation chemistry to polymerize some of those conducting polymers in aqueous solutions [16][17][18][19] thanks to the oxidation of dissolved organic monomers by oxidizing radicals in situ produced in the medium during water radiolysis. Additionally, pulse radiolysis was used to study and to understand the growth mechanism of PEDOT polymers initiated by these radicals in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…14 Apart from the traditional methods of polymers synthesis, ionizing radiation induced polymerization by g-rays or accelerated electrons is not commonly used in the field of CP synthesis. 15 In previous studies, our group has developed a new methodology based on radiation chemistry to polymerize some of those conducting polymers in aqueous solutions [16][17][18][19] thanks to the oxidation of dissolved organic monomers by oxidizing radicals in situ produced in the medium during water radiolysis. Additionally, pulse radiolysis was used to study and to understand the growth mechanism of PEDOT polymers initiated by these radicals in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of work have indicated that ·OH or H 2 O 2 can effectively initiate the oxidative polymerization of Py in an aqueous system under appropriate conditions. [11a,13] Commonly, H 2 O 2 or ·OH is introduced either directly or obtained indirectly by utilizing some chemical reactions. But it is well‐known that ·OH and H 2 O 2 can also be conveniently in situ produced when an aqueous solution is radiated by γ‐ray because they are the major active products of the radiolysis of water molecules, as well as the reductive active species of H· and e aq − .…”
Section: Resultsmentioning
confidence: 99%
“…The absorption at 1717 cm −1 should be due to the stretching vibration of CO in the unhydrolyzed ester bonds of PVA and the CO bonds at the pyrrole ring due to the reaction of the β‐C of the pyrrole ring and hydroxyl radicals, as reported in the previous literatures. [11a,18]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the broad applicability of IR spectroscopy and its chemical specificity, PTIR has enabled the characterization of diverse samples including: polymers [49,50], metal-organic frameworks [51], tri-halide perovskites [52,53], bacteria [43,54], cells [55,56], proteins [57] and drugs nanocrystals [58]. Recently our group applied the PTIR technique to measure high resolution absorption spectra and maps in the near-field surrounding PMMA coated of gold ASRRs which enabled the quantification of the SEIRA absorption enhancement with ≈ 100 nm resolution [3].…”
Section: Fabrication and Measurementsmentioning
confidence: 99%